Regional and outward economic integration in South-East Asia - Enzo Weber (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2007)
The subject of this paper tackles questions of macroeconomic integration of the South-East Asian countries South Korea, Singapore and Taiwan. Economically, the analysis is based on notions of stochastic long-run convergence and business cycle synchrony in the GDPs. According tests for cointegration and common serial correlation features reveal a high degree of coherence in long-run growth and medium-run fluctations. This allows extracting a common stochastic growth trend and a common business cycle. Further analysis shows, both of these compoments are subject to stronger influences from the US than from Japan. Convergence towards these matured economies conspicuously appears since the 1990s.
Keywords: E32; F15; C32; 330; Real Convergence; Cointegration; Common Cycles; South-East Asia; Konjunkturzusammenhang; Entwicklungskonvergenz; Südkorea; Singapur; Taiwan; Japan; USA